2018
DOI: 10.1167/tvst.7.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickening in Keratoconus Patients: Swept-Source Optical Coherence Tomography Study

Abstract: PurposeTo determine the choroidal thickness (CT) profile in keratoconus (KC) patients using swept-source optical coherence tomography (SS-OCT).MethodsThis was a prospective, cross-sectional study. One hundred two eyes of 52 KC patients were studied using Pentacam and SS-OCT. The macular CT profile was created by manually measuring the distance between the retinal pigment epithelium and the choroid-sclera junction on horizontal b-scans at nine different macular locations. The results were compared to 93 eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 43 publications
3
52
1
Order By: Relevance
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
“…Changes in CT profile in KC patients have already been described [21]. However, the exact changes taking place in the choroid itself are still unclear.…”
Section: Discussionmentioning
confidence: 96%
“…e main problem is thought to be related to collagen type I fibre degradation by metalloproteinases (MMP) [17]. Latest theories about KC hint to a possible inflammatory component in the pathology of this disease and that might explain the increase in their CT profile compared with healthy population [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, KCN is not associated with marked axial elongation [ 23 , 24 ]. Furthermore, it has been reported that choroidal thickness is increased in patients younger than 45 years old with KCN [ 25 ]. The observed higher frequency of KCN in our DSM patients warrants further investigation to determine if there is an association in terms of pathological disease process.…”
Section: Discussionmentioning
confidence: 99%